Injection-molded cerium-iron-boron composite magnet and method for producing the same
Patent Information
- Application Number
- CN202611300193.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-26
- Publication Date
- 2026-10-30
AI Technical Summary
然而,将铈铁硼磁粉应用于注塑成型面临着严峻挑战:首先,铈铁硼磁粉本身化学活性较高,易于氧化,导致磁性能衰减;其次,磁粉与高分子粘结剂之间的界面相容性差,易导致磁粉在基体中分散不均、界面结合弱,进而影响磁体的机械强度、密度及高温下的尺寸稳定性和磁稳定性
1.颠覆性的界面结合强度:由于形成了共价键连接的界面,磁粉与基体的剥离强度得到数量级提升。这直接转化为磁体极高的机械性能,径向压溃力可轻松超过280N,甚至达到300N以上,远超前代产品。
Smart Images

Figure CN123017722A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of rare earth permanent magnet composite materials technology, and specifically discloses an injection-molded cerium-iron-boron composite magnet and its preparation method. Background Technology
[0002] Rare earth permanent magnet materials are indispensable key functional materials in modern high-tech industries, widely used in new energy vehicles, wind power generation, consumer electronics, and industrial automation. Among them, neodymium iron boron (NdFeB) magnets dominate due to their excellent magnetic properties. However, key rare earth elements such as neodymium (Nd) and praseodymium (Pr) are expensive and have unstable supply, while rare earth elements with higher abundance, such as cerium (Ce) and lanthanum (La), are heavily stockpiled, resulting in a serious imbalance in the utilization of rare earth resources. Therefore, developing cerium iron boron magnets that partially or completely replace neodymium (Nd) with cerium (Ce) has become a research hotspot, aiming to reduce costs and promote the balanced utilization of rare earth resources.
[0003] In the prior art, CN118658720A discloses a "cerium iron boron magnet and its preparation method," which aims to improve the coercivity of sintered cerium iron boron magnets by adding PrCu alloy powder to cerium iron boron magnetic powder and combining it with specific sintering and aging processes. This technology belongs to the category of sintered magnets, and its preparation process is complex, energy-intensive, and the shape of the formed parts is limited, making it difficult to meet the needs of modern devices for complex-shaped and lightweight integrated magnets. Another prior art document, CN110911077B, proposes a "preparation method for high coercivity neodymium cerium iron boron magnets," which uses a dual-phase alloy mixed with copper-plated inorganic rare earth compound powder for sintering, utilizing in-situ reaction for grain boundary modification. This method is also based on sintering technology, and although it improves coercivity, it still faces the problems of long process flow and difficulty in preparing complex irregular-shaped parts.
[0004] Injection-molded bonded magnets have shown great potential due to their ability to mold complex structures in a single step, high production efficiency, and relatively low cost. However, applying cerium iron boron (CFeB) magnetic powder to injection molding faces significant challenges: First, CFeB magnetic powder itself has high chemical reactivity and is easily oxidized, leading to magnetic property decay; second, the poor interfacial compatibility between the magnetic powder and the polymer binder easily results in uneven dispersion of the magnetic powder in the matrix and weak interfacial bonding, thus affecting the mechanical strength, density, and dimensional and magnetic stability of the magnet at high temperatures. Existing injection-molded magnet technologies typically employ simple physical blending, failing to fundamentally solve the interfacial problem, resulting in overall performance, especially high-temperature aging resistance, often failing to meet the requirements of high-end applications.
[0005] Therefore, there is an urgent need in this field to develop a novel injection-molded cerium-iron-boron composite magnet and its preparation method, which can effectively improve the interface state between magnetic powder and polymer matrix through innovative material design, thereby significantly improving the mechanical properties and long-term reliability of the magnet while maintaining high magnetic performance. Summary of the Invention
[0006] The purpose of this invention is to provide an injection-molded cerium-iron-boron composite magnet and its preparation method.
[0007] This invention relates to the field of rare earth permanent magnet composite materials technology, specifically disclosing an injection-molded cerium-iron-boron composite magnet and its preparation method. The magnet is made from the following components: cerium-iron-boron magnetic powder with polymerizable double bonds introduced onto its surface via click chemistry; a reactive polymer binder that can undergo in-situ free radical copolymerization with the double bonds on the magnetic powder surface during injection molding; and other additives. The core of its preparation method lies in: firstly, constructing an active layer rich in carbon-carbon double bonds on the magnetic powder surface through the synergistic hydrolysis of a silane coupling agent and a hydroxyl-containing acrylate; subsequently, mixing this activated magnetic powder with a polyphenylene sulfide-based reactive binder containing unsaturated double bonds, an antioxidant, and a lubricant; under the high temperature and high pressure environment of injection molding, the initiator in the binder decomposes, initiating an in-situ interfacial copolymerization reaction between the double bonds on the magnetic powder surface and the double bonds in the binder, forming a robust "magnetic powder-polymer" covalent bond interfacial network. This invention fundamentally solves the problem of weak interfacial bonding caused by traditional physical mixing, enabling the magnet to maintain high magnetic properties (Br: 415-515 mT, Hcj: 565-695 kA / m) while exhibiting unprecedented heat aging resistance (surface magnetic attenuation ≤3.0% at 120℃ / 240h) and mechanical strength (radial crushing force ≥280N).
[0008] A type of injection-molded cerium-iron-boron composite magnet is prepared by in-situ interfacial polymerization reaction of the following raw materials in weight percentage: 85%-92% of the surface-modified cerium-iron-boron magnetic powder has polymerizable carbon-carbon double bonds; Reactive polymeric adhesives containing active unsaturated groups: 7%-14.2%; Free radical initiator 0.03%-0.1%; Other additives: 0.3%-0.6%.
[0009] Preferably, the cerium iron boron magnetic powder with polymerizable carbon-carbon double bonds is prepared by the following method: a bifunctional silane coupling agent containing both hydrolyzable siloxane groups and polymerizable acryloyloxy groups in its chain is pre-hydrolyzed in a solvent together with a hydroxyl-containing acrylate monomer, and then mixed and stirred with the cerium iron boron magnetic powder and dried to form a molecular layer on the surface of the magnetic powder anchored by Si-OM bonds and rich in polymerizable double bonds; the composition of the cerium iron boron magnetic powder, in atomic percentage, is RExFe100-xy-zZryBz, where RE is Pr, Nd, La and Ce, and the atomic percentage content of La and Ce in RE is 43%-57%, x=11.2at%-12.0at%, y=1.0at%-1.5at%, z=5.6at%-6.2at%.
[0010] Preferably, the bifunctional silane coupling agent is acryloyloxypropyltrimethoxysilane, and the hydroxyl-containing acrylate monomer is pentaerythritol triacrylate or hydroxyethyl methacrylate, with a mass ratio of 1:(0.5-2).
[0011] Preferably, the reactive polymeric adhesive containing active unsaturated groups is a polyphenylene sulfide-based polyurethane polymer with unsaturated double bonds in its side chains, obtained by reacting hydroxyl-terminated polyphenylene sulfide with excess diisocyanate to generate a hydroxyl-terminated isocyanate prepolymer, and then capping it with hydroxyl-containing acrylate monomers.
[0012] Preferably, the free radical initiator is any one of dicumyl peroxide, di-tert-butyl peroxide, or 1,1-di-tert-butylperoxide cyclohexane, and the temperature at which its half-life of 10 hours is matched with the injection molding temperature.
[0013] This invention also discloses a method for injection molding a cerium-iron-boron composite magnet, comprising the following steps: S1. Double bond modification of magnetic powder surface: Acryloyloxypropyltrimethoxysilane and pentaerythritol triacrylate were dissolved in an acetone / water mixed solvent in a certain ratio and pre-hydrolyzed for 30±2 minutes under an acidic catalyst; this hydrolysate was mixed with cerium iron boron magnetic powder, stirred at high speed and ultrasonically dispersed, and then vacuum dried at 60-80℃ to obtain activated magnetic powder with polymerizable double bonds on the surface; S2. Preparation of reactive adhesive: Hydroxyl-terminated polyphenylene sulfide is reacted with isophorone diisocyanate at 120-140℃ under nitrogen protection to generate terminal-NCO prepolymer; after cooling, hydroxyethyl methacrylate is added for end-capping reaction to obtain a polyphenylene sulfide-based polyurethane reactive adhesive containing unsaturated double bonds. S3. Premixing: The activated magnetic powder obtained in step S1, the reactive binder prepared in step S2, the free radical initiator, the antioxidant and the lubricant are put into a three-dimensional mixer and mixed for 6-8 hours under a protective atmosphere to obtain a homogeneous premix. S4. Injection Molding and In-situ Polymerization: The premix obtained in step S3 is directly fed into an injection molding machine and injection molded under the conditions of injection pressure of 90-120MPa, barrel temperature of 270-320℃ and mold temperature of 80-120℃. During this process, the free radical initiator is decomposed by heat, which triggers the double bonds on the surface of the magnetic powder to undergo an in-situ interfacial copolymerization reaction with the double bonds on the molecular chain of the reactive binder. After cooling, the composite magnet is obtained.
[0014] Preferably, the acidic catalyst is acetic acid, and its addition amount is 1%-3% of the mass of the silane coupling agent.
[0015] Preferably, in step S2, the molar ratio of the hydroxyl groups of the terminal hydroxyl polyphenylene sulfide, the NCO groups of the diisocyanate, and the hydroxyl groups of the capping monomer is 1 : (3.5-4.5) : (0.6-0.8).
[0016] Preferably, in step S3, the free radical initiator is added during the premixing stage, and its particle size D90 is less than 10 μm to ensure uniform dispersion in the premix.
[0017] The injection-molded cerium-iron-boron composite magnet prepared by this invention can be used in micro servo motors, automotive sensors, or robot joint motors that require high precision and high stability.
[0018] The core innovation of this invention lies in its departure from traditional physical coating or simple coupling, creatively combining "interfacial click chemistry" with "in-situ polymerization during injection molding" to construct a robust, three-dimensionally cross-linked interfacial layer dominated by covalent bonds between the magnetic powder and the polymer matrix. This represents a fundamental technological leap from "physical adsorption / simple coupling" to "in-situ covalent bonding."
[0019] First, we designed a complex magnetic powder surface engineering strategy. Instead of using a single silane coupling agent, we employed a "two-component synergistic modification" system: acryloyloxypropyltrimethoxysilane provides anchoring sites (Si-OM bonds) and the first polymerizable site (acryloyl group) for strong bonding with the magnetic powder surface, while simultaneously introducing multifunctional acrylates such as pentaerythritol triacrylate. The latter, through transesterification or hydrogen bonding with the hydrolysis intermediates of the silane via its hydroxyl groups, is "woven" into the surface layer, thereby introducing higher density and more functional polymerizable carbon-carbon double bonds onto the magnetic powder surface. This design transforms the magnetic powder surface from an inert entity into a highly active "polymerization reaction platform."
[0020] Second, we performed molecular-level design on the polymer binder, transforming it from a passive matrix material into an active "reactive companion" participating in interface construction. We synthesized polyphenylene sulfide-based polyurethanes with unsaturated double bonds in the side chains. The synthetic route is complex and not obvious: first, a prepolymer is generated by reacting terminal hydroxyl-terminated polyphenylene sulfide with diisocyanate; then, hydroxyl-containing acrylates (such as HEMA) are used for end-capping, precisely introducing the double bonds to the ends or side chains of the polymer chains. This design ensures that, in the molten state during injection molding, the binder molecules can carry reactive groups to migrate to the magnetic powder interface.
[0021] Third, the most innovative aspect lies in the concept of "using the injection molding machine as a chemical reactor." We uniformly disperse a thermally decomposable free radical initiator in the premix. The instant the material melts in the injection molding machine barrel and is pushed into the mold cavity, the initiator decomposes to generate free radicals. Instead of initiator-phase polymerization (which would lead to processing failure), it preferentially initiates an in-situ interfacial copolymerization reaction between the high-density double bonds on the surface of the magnetic powder and the double bonds on the adjacent reactive binder molecular chains. This process is similar to "click chemistry," rapidly and efficiently generating a copolymer "brush" or micro-crosslinked network at the interface between the two phases, "welding" the magnetic powder and polymer together with strong covalent bonds. This strategy of completing interfacial chemical bonding in a "one-step" process is something that those skilled in the art would find difficult to conceive of.
[0022] The in-situ interface aggregation mechanism is as follows: (1) Free radical initiators decompose at high injection molding temperatures to generate free radicals; (2) Free radicals attack carbon-carbon double bonds on the surface of magnetic powder; (3) The activated magnetic powder surface copolymerizes with the double bonds of the reactive binder; (4) Forming a robust covalent bond interface network; (5) Significantly enhances the interfacial bonding force between magnetic powder and polymer matrix; Magnetic powder -CH=CH2 + polymer -CH=CH2 + free radical → magnetic powder -CH-CH2- polymer (covalent bond).
[0023] Figure 3 The microscopic process of in-situ interfacial polymerization forming a covalent network is demonstrated. Under the high-temperature conditions of injection molding, the free radical initiator decomposes to generate free radicals (303). These free radicals attack the carbon-carbon double bonds on the surface of the activated magnetic powder (301) and the double bonds on the reactive polymer binder chains (304), initiating a copolymerization reaction between the two to form a strong covalent bond network (305). This covalent bond network "welds" the magnetic powder and the polymer matrix together, significantly enhancing the interfacial bonding strength, thereby improving the mechanical properties and thermal stability of the composite magnet.
[0024] Beneficial technical effects of the present invention: 1. Revolutionary interface bonding strength: Due to the formation of covalently bonded interfaces, the peel strength between the magnetic powder and the matrix is increased by orders of magnitude. This directly translates into extremely high mechanical properties of the magnet, with radial crushing force easily exceeding 280N, and even reaching over 300N, far surpassing previous generation products.
[0025] 2. Extreme long-term stability: The covalent bond energy is much higher than the physical force, and its bond energy is not sensitive to heat. Therefore, in high-temperature aging experiments, the magnetic powder is not easily debonded from the matrix, and the movement of polymer chain segments is severely restricted by chemical cross-linking points. This results in the magnetic property decay (≤3.0%) and size change (≤3μm) of the magnet reaching unprecedented low levels, and the lifespan is significantly extended.
[0026] 3. Optimized magnetic properties: The robust interface ensures that the magnetic powder is not easily detached or damaged during mixing and injection molding, maintaining the intrinsic properties of the magnetic powder. Simultaneously, the tight coating effectively inhibits the oxidation of the magnetic powder. Furthermore, the uniform interfacial stress distribution is beneficial for the orientation of the magnetic powder during injection molding, thereby achieving higher remanence and magnetic energy product.
[0027] 4. Integration and Innovation of the Process: The final interfacial bonding reaction is cleverly integrated into the final injection molding step, eliminating the need for additional post-processing steps and achieving "cross-linking during molding." This ensures both superior performance and improved production efficiency. Attached Figure Description
[0028] Figure 1 This is a schematic diagram of cerium iron boron magnetic powder with an organic-inorganic hybrid core-shell structure on the surface in an embodiment of the present invention (101 represents the organic active layer (containing polymerizable double bonds), 102 represents carbon-carbon double bonds (CH2=CH-), 103 represents the inorganic interface layer (Si-OM chemical bonds), and 104 represents the cerium iron boron magnetic powder particle matrix (core)).
[0029] Figure 2 This is a flowchart illustrating the manufacturing process of the injection-molded cerium-iron-boron composite magnet described in this invention.
[0030] Figure 3 This is a microscopic schematic diagram of the covalent network formed by the in-situ interfacial polymerization reaction described in this invention (301 represents activated magnetic powder, 302 represents carbon-carbon double bond (CH2=CH-), 303 represents free radical, 304 represents reactive polymer binder chain, and 305 represents covalent bond connection network). Detailed Implementation
[0031] Before further describing specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terminology used in the embodiments of the present invention is for describing specific embodiments and not for limiting the scope of protection of the present invention. Test methods in the following embodiments that do not specify specific conditions are generally performed under conventional conditions or as recommended by the respective manufacturers.
[0032] When numerical ranges are given in the embodiments, it should be understood that, unless otherwise stated in this invention, both endpoints of each numerical range and any value between the two endpoints may be selected. Unless otherwise defined, all technical and scientific terms used in this invention have the same meaning as commonly understood by those skilled in the art. In addition to the specific methods, apparatus, and materials used in the embodiments, based on the knowledge of those skilled in the art and the description of this invention, any prior art methods, apparatus, and materials similar to or identical to those described in the embodiments of this invention may be used to implement this invention.
[0033] Unless otherwise stated, the test methods, detection methods and preparation methods disclosed in this invention all adopt conventional techniques in this technical field.
[0034] Example 1
[0035] First, the magnetic powder surface was modified with double bonds. 1000g of cerium-iron-boron magnetic powder with a composition of RE=11.6at%, Zr=1.2at%, B=5.9at%, and LaCe accounting for 50at% of the total RE was placed in a high-speed mixer and preheated to 50°C. Then, 15g of acryloyloxypropyltrimethoxysilane and 15g of pentaerythritol triacrylate were dissolved together in a mixed solvent consisting of 200g of acetone and 5g of deionized water, and 0.3g of glacial acetic acid was added to catalyze a pre-hydrolysis reaction. This process was carried out at room temperature. The mixture was continuously magnetically stirred for 30 minutes to form a homogeneous pre-hydrolyzed solution. Then, under high-speed shear stirring, the pre-hydrolyzed solution was slowly sprayed into the magnetic powder in an atomized form, and stirring was continued for 60 minutes, supplemented by intermittent ultrasonic dispersion (600W power, 5 seconds on, 5 seconds off, total 15 minutes) to ensure that the magnetic powder particles were fully and uniformly impregnated and coated. After completion, the slurry was transferred to a vacuum drying oven and dried at 70℃ and -0.08MPa for 6 hours to obtain activated magnetic powder with a surface rich in high-density, highly reactive carbon-carbon double bonds. Next, a reactive binder was prepared. In a nitrogen-filled sealed reactor, 100g of hydroxyl-terminated polyphenylene sulfide with a hydroxyl value of 50mg KOH / g and 40g of isophorone diisocyanate were added, along with 0.1g of dibutyltin dilaurate as a catalyst. The system was gradually heated to 130℃ and reacted at this temperature for 3 hours. The reaction was monitored in real-time by online FTIR up to 2270cm⁻¹. -1The intensity of the -NCO characteristic absorption peak reached the theoretically calculated value, thus obtaining the terminal isocyanate prepolymer. The system was then cooled to 80°C, and 8 grams of hydroxyethyl methacrylate were slowly added dropwise for end-capping. The mixture was kept at this temperature and stirred for 2 hours until the -NCO peak essentially disappeared, yielding a polyphenylene sulfide-based reactive adhesive with methacrylate double bonds in the side chains, which was then granulated. Next, a premixing process was performed. 880 grams of the activated magnetic powder, 115 grams of the reactive adhesive, 0.5 grams of dicumyl peroxide, 3 grams of antioxidant 1076, and 1.5 grams of vinyl bis-stearamide were accurately weighed and placed in a three-dimensional motion mixer. Under continuous high-purity nitrogen protection, the mixture was stirred at 40 Hz for 7 hours to ensure uniform dispersion of the initiator powder and homogeneous mixing of all components. Finally, injection molding and in-situ polymerization are performed. The premixed material is directly fed into a precision injection molding machine. The barrel temperature is set to 290℃ (feeding section) / 300℃ (compression section) / 310℃ (metering section), the mold temperature is 100℃, the injection pressure is 100MPa, the holding pressure is 80MPa, and a medium injection speed is used. When the material melts and plasticizes in the barrel, dicumyl peroxide decomposes at high temperature to generate free radicals, which instantly trigger a rapid and efficient in-situ free radical copolymerization reaction between the dense double bonds on the surface of the magnetic powder and the double bonds on the binder molecular chain. This reaction continues and eventually solidifies during the process of high-speed injection of the material into the cavity and holding pressure and cooling. This forms a strong covalent bond network between the magnetic powder and the polymer matrix, directly producing standard sample columns and multi-pole magnetic rings with ultra-high interfacial bonding strength.
[0036] Example 2
[0037] First, the magnetic powder surface was modified with double bonds, following steps largely the same as in Example 1. The key difference was the adjustment of the surface modifier ratio. 15 g of acryloyloxypropyltrimethoxysilane and 10 g of pentaerythritol triacrylate were used for synergistic hydrolysis and coating to investigate the effect of a slightly lower double bond density on the final performance. Other conditions for magnetic powder treatment, such as solvent dosage, catalytic hydrolysis, stirring, ultrasonication, and vacuum drying parameters, remained consistent with Example 1. The synthetic route of the reactive binder was exactly the same as in Example 1, namely, reacting terminal hydroxyl polyphenylene sulfide with isophorone diisocyanate to generate a prepolymer, which was then end-capped with hydroxyethyl methacrylate to obtain the same PPS-UMA reactive binder. In the premixing stage, the raw material ratio was adjusted to 900g activated magnetic powder and 95g reactive binder. Simultaneously, the initiator was replaced with 0.4g of 1,1-di-tert-butylcyclohexane peroxide, which has a higher thermal decomposition temperature. 3.5g of antioxidant 1076 and 1.1g of vinyl bis-stearamide were added, and the mixture was carried out under nitrogen protection at the same rotation speed and duration. In the final injection molding and in-situ polymerization process, the temperature parameters were optimized. The barrel temperature was set at 280℃ (feeding section) / 295℃ (compression section) / 305℃ (metering section), the mold temperature was increased to 110℃, and the injection pressure was set to 95MPa. This process adjustment aimed to better match the decomposition characteristics of the initiator used, ensuring that the in-situ polymerization reaction was precisely triggered and completed during injection molding, thereby producing magnet samples with slightly different properties for comparative analysis.
[0038] Example 3
[0039] The formulation and process steps for the double bond modification of the magnetic powder surface were completely replicated in Example 1. Specifically, 15 grams of acryloyloxypropyltrimethoxysilane and 15 grams of pentaerythritol triacrylate were used to perform high-density double bond modification on the same batch of cerium iron boron magnetic powder to ensure that the surface activity of the magnetic powder was at the same level as in Example 1. The preparation of the reactive binder was also exactly the same as in Example 1, using hydroxyl-terminated polyphenylene sulfide and isocyanate end-capping technology to synthesize PPS-UMA. The main variable in this example was the composition of the premix. The amount of activated magnetic powder was adjusted to 860 grams, while the amount of reactive binder was increased to 135 grams, and the amount of initiator dicumyl peroxide was correspondingly increased to 0.7 grams to cope with the higher binder content and potentially more reaction sites. The amounts of antioxidant 1076 and lubricant vinyl bis-stearamide were slightly adjusted to 2.8 grams and 1.5 grams, respectively. The mixing process was still carried out under nitrogen protection for 7.5 hours. During the injection molding and in-situ polymerization stages, higher processing temperatures were adopted, with the barrel temperature set at 295℃ / 305℃ / 315℃, the mold temperature at 90℃, and the injection pressure at 105MPa. This adjustment aims to give the higher binder content system better fluidity and ensure that the increased initiator dosage can decompose fully and quickly, thereby initiating a more intense interfacial copolymerization reaction between the magnetic powder and the increased polymer, forming a denser cross-linked network, in order to obtain magnetic products that may have better mechanical strength and thermal stability.
[0040] Comparative Example 1 Comparative Example 1 serves as a reference for the traditional physical blending process, and its specific implementation is as follows: First, the magnetic powder undergoes a single surface treatment. 1000 grams of cerium iron boron magnetic powder is subjected to conventional silanization using only 15 grams of acryloyloxypropyltrimethoxysilane (without pentaerythritol triacrylate). The hydrolysis and coating processes are the same as in Example 1. The resulting magnetic powder surface has only a silane coupling agent layer and no high-density double bonds suitable for polymerization. The binder is directly a commercially available unmodified polyphenylene sulfide resin. During premixing, 880 grams of the silanized magnetic powder, 115 grams of ordinary PPS, 3 grams of antioxidant 1076, and 2 grams of lubricant are mixed in air for 6.5 hours without adding any free radical initiators. Subsequently, a traditional two-step process must be used: first, the premix is melt-blended and granulated at 300°C using a twin-screw extruder; then, the granulated material is injection molded. This process relies entirely on the physical adsorption and weak hydrogen bonding provided by the silane coupling agent to achieve interfacial bonding, without any chemical reaction, in order to simulate and compare the actual effects of existing technologies.
[0041] Comparative Example 2 Comparative Example 2 aimed to investigate the effect of magnetic powder activation alone without a reactive binder. The specific implementation was as follows: the magnetic powder treatment was exactly the same as in Example 1, using a two-component modification to obtain activated magnetic powder with a surface rich in double bonds. However, the binder was replaced with the same ordinary unmodified polyphenylene sulfide as in Comparative Example 1. In the premixing stage, 880 g of activated magnetic powder, 115 g of ordinary PPS, and specifically added 0.5 g of dicumyl peroxide (the same as in Example 1) as an initiator, along with 3 g of antioxidant 1076 and 1.5 g of lubricant, were mixed under nitrogen for 7 hours. Subsequently, molding was performed using the direct injection molding process of Example 1. Under this design, although the magnetic powder surface has active sites and an initiator is present, the binder molecular chain lacks corresponding unsaturated double bonds as the other party in the copolymerization reaction, preventing an effective in-situ interfacial copolymerization reaction. The presence of the initiator can only cause homopolymerization or ineffective decomposition of the double bonds on the magnetic powder surface, thus isolating the necessity of a reactive binder in the system.
[0042] Comparative Example 3 Comparative Example 3 aimed to investigate the effect of using only a reactive binder without any active magnetic powder. The specific implementation was as follows: Unmodified cerium-iron-boron magnetic powder was used directly, with a natural oxide layer on its surface, lacking polymerizable double bonds. The binder used was the same self-synthesized PPS-UMA reactive binder as in Example 1. During premixing, 880 g of unmodified magnetic powder, 115 g of PPS-UMA reactive binder, 0.5 g of dicumyl peroxide, 3 g of antioxidant 1076, and 1.5 g of lubricant were mixed under nitrogen protection for 7 hours. The mixture was then molded using a direct injection molding process. In this case, although the binder was reactive and an initiator was present, the chemically inert surface of the magnetic powder lacked anchoring points for "click" reactions. Free radicals could not initiate effective covalent bonding at the interface, and the reaction was mainly confined to the binder matrix or occurred with impurities. This demonstrates that double bond modification of the magnetic powder surface is an indispensable prerequisite for achieving interfacial covalent bonding.
[0043] Comparative Example 4 Comparative Example 4 aimed to verify the criticality of the timing design of "in-situ reaction during injection molding," and was implemented as follows: its material composition was exactly the same as that of Example 1, using 880 grams of double-bonded activated magnetic powder, 115 grams of PPS-UMA reactive binder, 0.5 grams of dicumyl peroxide, and an equal amount of additives, and the premixing process was also the same. However, the key process difference was that this premix containing the initiator was fed into a twin-screw extruder for melt granulation. Under the extruder's set high temperature of 300°C and strong mechanical shearing, dicumyl peroxide was prematurely and extensively decomposed, causing the in-situ polymerization reaction to occur uncontrollably and violently during the granulation stage. As a result, the extruded material had undergone varying degrees of partial cross-linking, manifested as a darker granule color and a more brittle texture. When attempting to injection mold this pre-reacted granule, the material's fluidity was drastically lost, and even with the injection pressure increased to the equipment's upper limit of 120 MPa, the mold cavity could not be filled, ultimately failing to yield a complete and formed magnet sample. This comparative example, through a counterexample of process failure, powerfully demonstrates the necessity of precisely controlling the final polymerization reaction at the final injection molding moment.
[0044] Comparative Example 5 Comparative Example 5 serves as a reference for sintered magnet technology, and its implementation is entirely based on Example 2 of Prior Art Document 1 (CN118658720A): First, a cerium-iron-boron alloy was prepared with the following composition by mass percentage: Ce-14.6%, Nd-11.7%, Pr-3.9%, Gd-1.8%, B-0.95%, Ti-0.12%, Zr-0.17%, Cu-0.03%, Al-0.06%, Co-0.09%, with the balance being Fe. This alloy was then processed into strips using a melt quenching process. Subsequently, hydrogen explosion treatment was performed to obtain fragments, and after adding an antioxidant, the fragments were subjected to air jet milling to obtain an average particle size of 2. 6-micron magnetic powder was then mixed with 2% by weight of Pr68Cu32 alloy powder and pressed into a blank under an orientation magnetic field of 1.8T and an isostatic pressure of 200MPa. Finally, sintering and aging treatment were carried out: the temperature was raised to 1050℃ at 1.5℃ / min and held for 3 hours in a vacuum sintering furnace, followed by two-stage aging. In the first stage, the temperature was raised to 880℃ at 2℃ / min and held for 1 hour, and in the second stage, the temperature was raised to 500℃ at 2℃ / min and held for 2 hours. Finally, a high-density sintered cerium iron boron magnet was obtained and wire-cut into a multi-pole magnetic ring with the same shape and size as in Example 1 for performance comparison testing.
[0045] Performance testing Testing standards: Magnetism (Br), coercivity (Hcb), intrinsic coercivity (Hcj), and maximum energy product ((BH)max) are based on standard GB / T3217-2013; radial crushing force is based on GB / T 44656-2024; dimensional variations are based on GB / T 41739-2022. Table 1 shows the performance test results of various embodiments of the present invention.
[0046] Table 2 shows the performance test results of each comparative example of the present invention.
[0047] Analysis of Tables 1 and 2 reveals the possible causes of the differences in test results: 1. Significant improvement in magnetic and mechanical properties (compare examples with Comparative Examples 1-4): Examples 1-3 demonstrate optimal overall performance. The fundamental reason lies in the successful in-situ interfacial copolymerization. The high-density double bonds on the magnetic powder surface and the double bonds of the reactive binder copolymerize via free radicals, forming a robust, predominantly covalent interfacial layer. This "welding" effect significantly enhances stress transfer efficiency, resulting in the highest radial crushing force. Simultaneously, the robust interface protects the magnetic powder, reducing damage and oxidation during processing, and allowing for more complete orientation of the magnetic powder in a magnetic field, thus optimizing magnetic properties.
[0048] Comparative Example 1 (traditional physical blend) has the weakest interfacial bonding, relying only on van der Waals forces and a small number of possible hydrogen bonds. Therefore, the magnetic powder is prone to agglomeration and debonding from the matrix, resulting in the worst performance in all aspects.
[0049] Comparative Example 2 (activated magnetic powder only) shows that even if there are double bonds on the surface of the magnetic powder, if the binder does not provide reaction sites, the presence of the initiator cannot promote effective interfacial copolymerization, resulting in limited performance improvement, which mainly depends on the improvement of physical coating.
[0050] Comparative Example 3 (reactive binder only) shows that if the magnetic powder surface is inert and lacks reaction anchoring points, the reactive binder and initiator cannot effectively "take root" at the interface, and the performance improvement is also limited.
[0051] The failure of Comparative Example 4 directly demonstrates the criticality of the timing design of "in-situ reaction during injection molding." Premature reaction during the granulation stage leads to cross-linking of the material and loss of processing fluidity, which conversely confirms the non-obviousness and ingenuity of the process design of this invention.
[0052] 2. Excellent thermal stability: The embodiment exhibits minimal performance degradation after thermal aging. This is because the thermal stability of the covalent bond interface network is far greater than that of physical forces. This network acts like a rigid "cage," firmly securing the magnetic powder and significantly suppressing chain segment movement and creep in the polymer matrix at high temperatures, thereby ensuring extreme stability in both magnetic properties and dimensions.
[0053] Comparative Examples 1-4 showed weak interfacial bonding, making the interface prone to damage at high temperatures. This led to relaxation of the polymer chains, resulting in magnetic powder displacement and accelerated oxidation, thus causing severe attenuation.
[0054] Although the sintered magnet of Comparative Example 5 has high magnetic properties after aging, its grain boundary phase may undergo element diffusion, oxidation or phase transformation under long-term thermal aging, resulting in irreversible decay of magnetic properties (especially coercivity), and its decay mechanism is completely different from that of bonded magnets.
[0055] Conclusion: The test results fully demonstrate that this invention successfully constructs a strong covalent bond interface between cerium iron boron magnetic powder and the polymer matrix through the synergistic approach of "magnetic powder surface double bonding," "reactive binder design," and "in-situ polymerization during injection molding." This innovative structure endows injection-molded cerium iron boron composite magnets with mechanical strength and long-term thermal stability far exceeding those of traditional methods, while maintaining excellent magnetic properties, thus solving a long-standing technical bottleneck in this field. All comparative examples failed to simultaneously achieve the comprehensive performance level of the embodiment, highlighting the inventiveness and technological advancement of this invention.
[0056] Finally, it should be noted that the above embodiments are used to illustrate the technical solutions of the present invention and not to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A type of injection-molded cerium-iron-boron composite magnet, characterized in that, It is prepared by in-situ interfacial polymerization of the following raw materials in weight percentage: 85%-92% of the surface-modified cerium-iron-boron magnetic powder has polymerizable carbon-carbon double bonds; Reactive polymeric adhesives containing active unsaturated groups: 7%-14.2%; Free radical initiator 0.03%-0.1%; Other additives: 0.3%-0.6%.
2. The injection-molded cerium-iron-boron composite magnet according to claim 1, characterized in that, The cerium iron boron magnetic powder with polymerizable carbon-carbon double bonds on its surface is prepared by the following method: a bifunctional silane coupling agent containing both hydrolyzable siloxane groups and polymerizable acryloyloxy groups in its chain is pre-hydrolyzed in a solvent together with a hydroxyl-containing acrylate monomer, and then mixed and stirred with the cerium iron boron magnetic powder and dried to form a molecular layer on the surface of the magnetic powder anchored by Si-OM bonds and rich in polymerizable double bonds; the composition of the cerium iron boron magnetic powder, in atomic percentage, is RExFe100-xy-zZryBz, where RE is Pr, Nd, La and Ce, and the atomic percentage content of La and Ce in RE is 43%-57%, x=11.2at%-12.0at%, y=1.0at%-1.5at%, z=5.6at%-6.2at%.
3. The injection-molded cerium-iron-boron composite magnet according to claim 2, characterized in that: The bifunctional silane coupling agent is acryloyloxypropyltrimethoxysilane, and the hydroxyl-containing acrylate monomer is pentaerythritol triacrylate or hydroxyethyl methacrylate, with a mass ratio of 1:(0.5-2).
4. The injection-molded cerium-iron-boron composite magnet according to claim 1, characterized in that: The reactive polymeric adhesive containing active unsaturated groups is a polyphenylene sulfide-based polyurethane polymer with unsaturated double bonds in its side chains, obtained by reacting hydroxyl-terminated polyphenylene sulfide with excess diisocyanate to generate hydroxyl-terminated isocyanate prepolymer, and then capping it with hydroxyl-containing acrylate monomers.
5. The injection-molded cerium-iron-boron composite magnet according to claim 1, characterized in that, The free radical initiator is any one of dicumyl peroxide, di-tert-butyl peroxide, or 1,1-di-tert-butylperoxide cyclohexane, and its half-life of 10 hours is matched with the injection molding temperature.
6. A method for preparing an injection-molded cerium-iron-boron composite magnet as described in any one of claims 1-5, characterized in that, Includes the following steps: S1. Double bond modification of magnetic powder surface: Acryloyloxypropyltrimethoxysilane and pentaerythritol triacrylate were dissolved in an acetone / water mixed solvent in a certain ratio and pre-hydrolyzed for 30±2 minutes under an acidic catalyst; this hydrolysate was mixed with cerium iron boron magnetic powder, stirred at high speed and ultrasonically dispersed, and then vacuum dried at 60-80℃ to obtain activated magnetic powder with polymerizable double bonds on the surface; S2. Preparation of reactive adhesive: Hydroxyl-terminated polyphenylene sulfide is reacted with isophorone diisocyanate at 120-140℃ under nitrogen protection to generate terminal-NCO prepolymer; after cooling, hydroxyethyl methacrylate is added for end-capping reaction to obtain a polyphenylene sulfide-based polyurethane reactive adhesive containing unsaturated double bonds. S3. Premixing: The activated magnetic powder obtained in step S1, the reactive binder prepared in step S2, the free radical initiator, the antioxidant and the lubricant are put into a three-dimensional mixer and mixed for 6-8 hours under a protective atmosphere to obtain a homogeneous premix. S4. Injection Molding and In-situ Polymerization: The premix obtained in step S3 is directly fed into an injection molding machine and injection molded under the conditions of injection pressure of 90-120MPa, barrel temperature of 270-320℃ and mold temperature of 80-120℃. During this process, the free radical initiator is decomposed by heat, which triggers the double bonds on the surface of the magnetic powder to undergo an in-situ interfacial copolymerization reaction with the double bonds on the molecular chain of the reactive binder. After cooling, the composite magnet is obtained.
7. The method according to claim 6, characterized in that: In step S1, the acidic catalyst is acetic acid, and its addition amount is 1%-3% of the mass of the silane coupling agent.
8. The method according to claim 6, characterized in that: In step S2, the molar ratio of the hydroxyl groups of the hydroxyl-terminated polyphenylene sulfide, the NCO groups of the diisocyanate, and the hydroxyl groups of the capping monomer is 1 : (3.5-4.5) : (0.6-0.8).
9. The method according to claim 6, characterized in that: In step S3, the free radical initiator is added during the premixing stage, and its particle size D90 is less than 10 μm to ensure uniform dispersion in the premix.
10. The application of an injection-molded cerium-iron-boron composite magnet prepared by the method according to any one of claims 6-9 in micro servo motors, automotive sensors, or robot joint motors requiring high precision and high stability.
Citation Information
Patent Citations
A method for preparing a high coercivity neodymium cerium iron boron magnet
CN110911077B
Cerium-iron-boron magnet and preparation method thereof
CN118658720A
